Laminography in the lab: imaging planar objects using a conventional x-ray CT scanner. (11th February 2019) - Fisher, S L; Holmes, D J; Jørgensen, J S; Gajjar, P; Behnsen, J; Lionheart, W R B; Withers, P J
Abstract: Whilst x-ray micro-computed tomography (CT) machines have developed into a popular laboratory tool for non-destructive 3D imaging of materials, they are not well-suited for scanning flat objects, for which there is an increasing demand. Computed laminography (CL) techniques have been developed for imaging planar samples such as fossils, paintings, printed circuit boards and composite panels. This paper is the first work demonstrating how CL may be implemented on a conventional industrial laboratory micro-CT scanner, without the need for specialist equipment. A rotary CL scan configuration (also known as tilted or oblique CT) was successfully implemented, and the projection images reconstructed using the conjugate gradient least squares (CGLS) method. Computer simulations were used to analyse the causes of image artefacts seen in the cone-beam CL reconstructions, and to devise corrections for them. The resulting laboratory CL method produces reconstructions with fewer artefacts and a more isotropic resolution compared to limited-angle scan configurations otherwise used for planar samples. This demonstrates that CL can be performed in the laboratory without specialist equipment beyond that required for standard CT5 .